2022
DOI: 10.1039/d2fo01448c
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of pectic oligosaccharides on acute colitis model mice: modulating epithelial barrier, gut microbiota and Treg/Th17 balance

Abstract: Pectin as dietary fiber supplements has shown emerging potential in clinical ulcerative colitis (UC) adjuvant therapy. In this study, the preventive and prebiotic effect of enzymatic-degraded pectic oligosaccharides (POS) was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…26,27 The findings of our previous studies suggest that various functional foods possess prebiotic properties by modulating the Treg/ Th17 cell balance. 28,29 On the other hand, there has been limited research on the impact of STA on the crucial pathogenic mechanism of Treg/Th17 balance in UC. In the present study, we initially assessed Treg and Th17 activities in DSS-induced colitis model mice treated with STA (Figure 3).…”
Section: ■ Discussionmentioning
confidence: 99%
“…26,27 The findings of our previous studies suggest that various functional foods possess prebiotic properties by modulating the Treg/ Th17 cell balance. 28,29 On the other hand, there has been limited research on the impact of STA on the crucial pathogenic mechanism of Treg/Th17 balance in UC. In the present study, we initially assessed Treg and Th17 activities in DSS-induced colitis model mice treated with STA (Figure 3).…”
Section: ■ Discussionmentioning
confidence: 99%
“…16,45–47 As an emerging prebiotic, POS has been shown to regulate gut microbiota and play a preventive/therapeutic role in various diseases. 26,48–51 Pectic is involved in a wide range of biological effects, including the suppression of obesity, fatty liver disease, microbiologic inflammation, increased gastrointestinal barrier function and immune strengthening activity by regulating gut microbiota. 52 However, Li et al (2021) suggested that in vivo absorption is difficult for macromolecules, 53 implying that the high molecular weight (Mw) and complex structures of natural pectins limit their bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…23 In our previous study, we innovatively utilized enzymatic degradation to generate POS with DP3 as the main by-product, which demonstrated anti-inflammatory activity in a mouse model of DSS-induced colitis and modulating gut microbiota. 26 However, the specific role and potential mechanism of POS in the treatment of obesity have not yet been elucidated. Our study demonstrates that enzymatically degraded POS significantly affects HFD-induced obesity in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA of gathered fecal samples were abstracted for PCR amplification and 16S RNA sequencing based on a previous description [ 58 ]. Subsequently, data analysis method of gut microbiota distribution and structure were from our previous study [ 58 ].…”
Section: Methodsmentioning
confidence: 99%